2021
DOI: 10.33448/rsd-v10i10.19004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil type on mean annual increment, wood anatomy and properties of 33-year-old Corymbia citriodora (Hook.), K. D. Hill, & L. A. S. Johnson

Abstract: This study aimed to determine the effects of physical, chemical and water-holding capacity of Quartzarenic Neosol, Red Latosol and Red Nitosol on tree growth, physicomechanical properties and anatomical features of wood from 33-year-old C. citriodora plantations. More clayey soils with higher water availability, such as Red Latosol and Red Nitosol, increased the mean annual increment and heartwood percentage. In more sandy soils, such as Quartzarenic Neosol, density increased, but the size and diameter of fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Several studies have emphasized the importance of evaluating soil properties to determine productivity and wood quality at different sites, addressing edaphic factors in general or specific soil characteristics (Alfaro-Sánchez et al 2019;Almeida et al 2020;Caldeira et al 2020;Maidana et al 2021;Oliveira et al 2021;Rubilar et al 2020;Vieira et al 2021). Overall, these studies have found significant effects of soil characteristics on growth and wood quality proprieties.…”
Section: R a F Tmentioning
confidence: 99%
“…Several studies have emphasized the importance of evaluating soil properties to determine productivity and wood quality at different sites, addressing edaphic factors in general or specific soil characteristics (Alfaro-Sánchez et al 2019;Almeida et al 2020;Caldeira et al 2020;Maidana et al 2021;Oliveira et al 2021;Rubilar et al 2020;Vieira et al 2021). Overall, these studies have found significant effects of soil characteristics on growth and wood quality proprieties.…”
Section: R a F Tmentioning
confidence: 99%